Cathode active material for lithium ion secondary battery, lithium ion secondary battery and method for manufacturing cathode active material for lithium ion secondary battery
The introduction of a manganese-rich and zirconium-rich lithium transition metal composite oxide as a positive electrode active material in lithium-ion secondary batteries addresses the suboptimal discharge capacity, enhancing energy efficiency and reducing battery requirements.
Patent Information
- Application Number
- JP2023168780
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2043-09-28
AI Technical Summary
Current lithium-ion secondary batteries have a discharge capacity at 4.35-2.75V of about 150-170mAh/g, which is not optimal and requires improvement for enhanced energy efficiency.
A positive electrode active material composed of lithium transition metal composite oxide, specifically in the form of particles with a manganese-rich outer layer and a zirconium-rich surface, represented by the formula Li1.0-1.04Ni0.47-0.58Mn0.40-0.50Zr0.005-0.02O2, which enhances the discharge capacity and cycle characteristics.
The proposed positive electrode active material significantly increases the discharge capacity of lithium-ion secondary batteries, reduces the number of batteries required, and improves energy efficiency by optimizing the Mn/Ni ratio and suppressing valence changes.
Smart Images

Figure 2025058687000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery, a lithium ion secondary battery, and a method for producing a positive electrode active material for a lithium ion secondary battery. [Background technology]
[0002] In recent years, research and development has been conducted on secondary batteries that contribute to energy efficiency. In particular, lithium-ion secondary batteries are becoming increasingly important as a power source for electric vehicles (EVs) and hybrid electric vehicles (HEVs).
[0003] Positive electrode active materials have been attracting attention as important components that determine the capacity of lithium ion secondary batteries, and their development is being promoted. For example, composite oxides in which part of the nickel and manganese in lithium nickel manganese composite oxide is replaced with zirconium (Zr) have been reported as positive electrode active materials for use in lithium ion secondary batteries (e.g., Non-Patent Document 1 and Patent Document 1). [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Yao, et al., “Facile synthesis of Li2ZrO3-modified LiNi0.5Mn0.5O2 cathode material from a mechanical milling route for lithium-ion batteries” Journal of Electroceramics. 43, 84-91 (2019) [Patent documents]
[0005] [Patent Document 1] International Publication No. 2020 / 209239 Brochure Summary of the Invention
Problems to be Solved by the Invention
[0006] In Non-Patent Document 1 and Patent Document 1, the discharge capacity at 4.35 to 2.75 V is about 150 to 170 mAh / g, leaving room for improvement.
[0007] The present invention has been made to solve the above problems, and an object thereof is to provide a positive electrode active material for a lithium ion secondary battery capable of obtaining a lithium ion secondary battery with a higher discharge capacity, a lithium ion secondary battery using the positive electrode active material, and a method for manufacturing a positive electrode active material for a lithium ion secondary battery. And, by extension, it contributes to the improvement of energy efficiency.
Means for Solving the Problems
[0008] To achieve the above object, the present invention provides the following means. [1] A positive electrode active material for a lithium ion secondary battery mainly composed of a lithium transition metal composite oxide, wherein the lithium transition metal composite oxide is in the form of particles having an outer layer on the surface, the lithium transition metal composite oxide is represented by the following formula (1), Li m Ni x Mn y Zr z O2(1) (In formula (1), m is in the range of 1.0 ≦ m ≦ 1.04, x is in the range of 0.47 < x < 0.58, y is in the range of 0.40 ≦ y < 0.50, and z is in the range of 0 < z < 0.02) A positive electrode active material for a lithium ion secondary battery, wherein the ratio (Mn / Ni ratio) of the number of Mn atoms to the number of Ni atoms in the outer layer is 1.0 or more and 2.5 or less.
[0009] The surface of the positive electrode active material for lithium ion secondary batteries according to [1] is manganese-rich. Therefore, even if the Ni content is reduced, the discharge capacity can be increased. Therefore, in a lithium ion secondary battery using the positive electrode active material, the number of batteries required can be reduced, which contributes to cost reduction. In other words, it can contribute to energy efficiency.
[0010] [2] The positive electrode active material for a lithium ion secondary battery according to [1], wherein a ratio of the number of Ni atoms to the number of Zr atoms in the outer layer (Ni / Zr ratio) is 6.50 or more and 17.5 or less.
[0011] The positive electrode active material for lithium ion secondary batteries according to [2] has a zirconium (Zr)-rich surface. This makes it possible to suppress an increase in Ni valence and a decrease in Mn valence, and further increase the discharge capacity. In addition, the cycle characteristics can be further improved. This contributes to further energy efficiency.
[0012] [3] Solid-state lithium nuclear magnetic resonance analysis using magic angle sample spinning ( 6 The positive electrode active material for a lithium ion secondary battery according to [1] or [2], wherein the lithium transition metal composite oxide has a peak in the range of 500 to 800 ppm in a spectrum measured by Li-MAS-NMR.
[0013] The positive electrode active material for lithium ion secondary batteries according to [3] has a peak in the range of 500 to 800 ppm. This means that Ni and Mn in the transition metal layer adjacent to the Li-O6 resulting from the Li layer are uniformly dissolved in solid solution. This contributes to further energy efficiency.
[0014] [4] Solid-state lithium nuclear magnetic resonance analysis using magic angle sample spinning ( 6 The positive electrode active material for a lithium ion secondary battery according to any one of [1] to [3], wherein a spectrum of the lithium transition metal composite oxide measured by Li-MAS-NMR does not have a peak in the range of 1475 to 1550 ppm.
[0015] The positive electrode active material for lithium ion secondary batteries according to [4] has no peak in the range of 1475 to 1550 ppm. This means that there is no peak due to Li2MnO3, and indicates that there is no LiMn6 domain in the transition metal layer. This contributes to further energy efficiency.
[0016] [5] The positive electrode active material for a lithium ion secondary battery according to any one of [1] to [4], which has no peak in the range of 42°≦2θ≦43° in an X-ray diffraction pattern obtained using a Cu radiation source.
[0017] The positive electrode active material for lithium ion secondary batteries according to [5] does not have a peak in the range of 42°≦2θ≦43°. This means that there is no peak due to Li2ZrO3, and indicates that Zr is dissolved in the lithium transition metal composite oxide. This can contribute to further energy efficiency.
[0018] [6] The positive electrode active material for a lithium ion secondary battery according to any one of [1] to [5], wherein in an X-ray diffraction pattern using a Cu radiation source, the peaks of the 108 plane and the 110 plane in the space group R-3m are split, and the half-value width of the peak of the 110 plane is 0.10° or more and 0.21° or less.
[0019] In the positive electrode active material for lithium ion secondary batteries according to [6], the peaks of the 108 plane and the 110 plane are split, and the half-width of the peak of the 110 plane is 0.10° or more and 0.21° or less. This indicates that Ni, Mn, and Zr are uniformly dispersed without phase separation. In other words, Ni, Mn, and Zr are not phase separated in the lithium transition metal composite oxide, but are in solid solution. This can contribute to further energy efficiency.
[0020] [7] The positive electrode active material for a lithium ion secondary battery according to any one of [1] to [6], wherein the lithium transition metal composite oxide has lattice constants (a, c, c / a) in a space group R-3m such that the a-axis length is 2.880 Å to 2.900 Å, the c-axis length is 14.28 Å to 14.30 Å, and c / a is 4.940 to 4.960.
[0021] The positive electrode active material for lithium ion secondary batteries according to [7] has a lattice constant that satisfies a specific range. Therefore, the lithium transition metal composite oxide has low resistance and allows lithium ions to easily diffuse within the particles. This contributes to further energy efficiency.
[0022] [8] A lithium ion secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode contains the positive electrode active material for lithium ion secondary batteries according to any one of [1] to [7].
[0023] [8] The positive electrode of the lithium ion secondary battery contains the positive electrode active material for lithium ion secondary batteries. This can increase the discharge capacity, reduce the number of batteries required, and contribute to cost reduction. In other words, it can contribute to energy efficiency.
[0024] [9] A method for producing a positive electrode active material for a lithium ion secondary battery according to any one of [1] to [7], A method for producing a positive electrode active material for a lithium ion secondary battery, comprising a step of heat-treating a mixture of a lithium compound, a zirconium compound, and a nickel manganese compound, or a mixture of a lithium compound and a nickel manganese zirconium compound, at 1025°C or higher and 1150°C or lower for 1 minute or longer and 7 hours or shorter.
[0025] By using the method including the above-mentioned heat treatment step, it is possible to produce a positive electrode active material for a lithium ion secondary battery that satisfies the range of the chemical composition of the lithium transition metal composite oxide represented by formula (1) and the Mn / Ni ratio in the outer layer.
[0026]
[10] The method for producing a positive electrode active material for a lithium ion secondary battery according to [9], further comprising the step of subsequently holding the obtained lithium transition metal composite oxide at 450°C or higher and 800°C or lower for 1 hour or longer and 24 hours or shorter after the heat treatment step.
[0027] By further providing the above-mentioned holding step (slow cooling step), it is possible to suppress the decrease in the valence of Mn in the lithium transition metal composite oxide and to obtain a more stable structure. This makes it possible to further increase the discharge capacity. In addition, it makes it possible to further improve the cycle characteristics. This can therefore contribute to further energy efficiency. Effect of the Invention
[0028] According to the positive electrode active material for a lithium ion secondary battery, the lithium ion secondary battery, and the method for producing a positive electrode active material for a lithium ion secondary battery of the present invention, the discharge capacity can be further increased. [Brief description of the drawings]
[0029] [Figure 1] 1 is a graph showing 6Li-MAS-NMR spectra of the lithium transition metal composite oxides of Examples 1 and 2. [Diagram 2] FIG. 2 is a diagram showing powder X-ray diffraction patterns of the lithium transition metal composite oxides of Examples 1 and 2. [Diagram 3] 1 is a cross-sectional view showing a schematic diagram of a lithium-ion secondary battery according to one embodiment of the present invention. [Figure 4] 2 is a graph showing charge / discharge curves of lithium ion secondary batteries using the lithium transition metal composite oxides of Examples 1 and 2. [Diagram 5] 1 is a graph showing 6Li-MAS-NMR spectra of the lithium transition metal composite oxides of Example 3 and Comparative Example 1. [Figure 6] FIG. 2 is a diagram showing powder X-ray diffraction patterns of the lithium transition metal composite oxides of Example 3 and Comparative Example 1. [Figure 7] 1 is a graph showing charge / discharge curves of lithium ion secondary batteries using the lithium transition metal composite oxides of Example 3 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] Preferred embodiments of the present invention will now be described in detail.
[0031] [Positive electrode active material for lithium-ion secondary batteries] The positive electrode active material for lithium ion secondary batteries of this embodiment is mainly composed of lithium transition metal composite oxide and is used for the positive electrode of lithium ion secondary batteries. The term "mainly composed of" lithium transition metal composite oxide means that the content of lithium transition metal composite oxide is 75 mass% or more, preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more, based on the total mass of the positive electrode active material, and may be 100 mass%. As long as the function of the present invention is not impaired, the positive electrode active material for lithium ion secondary batteries may contain components other than the main component.
[0032] The positive electrode active material for a lithium ion secondary battery of this embodiment may contain only one type of lithium transition metal composite oxide or may contain two or more types of lithium transition metal composite oxide, so long as it contains a lithium transition metal composite oxide as a main component.
[0033] When a positive electrode active material is produced using a lithium transition metal composite oxide as a main component, the composition ratio (Li:Ni:Mn:Zr) of the entire lithium transition metal composite oxide is maintained in the obtained positive electrode active material. When a positive electrode active material obtained using a lithium transition metal composite oxide having such a composition as a main component is used in a secondary battery, a high capacity can be realized. In addition, the composition ratio of the lithium transition metal composite oxide is adjusted to be the same as the composition ratio required for the positive electrode active material to be obtained.
[0034] (Lithium transition metal complex oxide) The lithium transition metal composite oxide of this embodiment is a layered rock salt type oxide, and is in the form of particles having an outer layer on the surface.
[0035] In this specification, the average particle diameter of the particles of the lithium transition metal composite oxide (hereinafter, also simply referred to as "average particle diameter") is not particularly limited, but for example, 0.25 to 10 μm is preferable, 0.25 to 5.0 μm is more preferable, and 0.50 to 2.5 μm is even more preferable. When the average particle diameter is equal to or greater than the above lower limit value, the productivity of the positive electrode active material for the lithium ion secondary battery can be further enhanced. When the average particle diameter is equal to or less than the above upper limit value, the electrochemical characteristics of the lithium ion secondary battery can be made better. The average particle diameter means, for example, D50 measured by a laser diffraction particle size distribution measuring device or the like.
[0036] <Chemical composition> In a conventional lithium transition metal composite oxide (for example, LiNi 0.5 Mn 0.5 O2), when Li is dissolved in the transition element, Ni 2+ involved in the redox reaction is converted to Ni 3+ . Therefore, in order to improve the electrochemical characteristics as the positive electrode active material, it is necessary to increase the amount of Ni used. The present invention is based on the finding that by adding Zr as a constituent element to LiNi 0.5 Mn 0.5 O2 and replacing a part of Ni 0.5 Mn 0.5 with Li and Zr, an increase in the valence of Ni ions to 3 can be suppressed. Thereby, in the present invention, the amount of Ni used can be reduced while maintaining good electrochemical characteristics of the positive electrode active material.
[0037] The lithium transition metal composite oxide of the present embodiment is represented by the following formula (1). Li m Ni x Mn y Zr z O2(1) In formula (1), m is in the range of 1.0 ≦ m ≦ 1.04, x is in the range of 0.47 < x < 0.58, y is in the range of 0.40 ≦ y < 0.50, and z is in the range of 0 < z < 0.02.
[0038] More preferably, in the lithium transition metal composite oxide of the present embodiment, m in formula (1) is in the range of 1.02≦m≦1.04, x is in the range of 0.475≦x≦0.55, y is in the range of 0.45≦y≦0.475, and z is in the range of 0.005≦z≦0.015. 1.02 Ni 0.55 Mn 0.475 Zr 0.005 O2 to Li 1.04 Ni 0.475 Mn 0.45 Zr 0.015 In the O2 range.
[0039] The chemical composition of the lithium transition metal composite oxide of this embodiment can be determined by inductively coupled plasma (ICP) atomic emission spectrometry.
[0040] <Surface composition> The lithium transition metal composite oxide particles have an outer layer on their surfaces. In this specification, the "outer layer" refers to the region from the surface of the particle to a depth of 25 nm toward the inside of the particle. When the particle diameter is less than 50 nm, the particle is considered to have a single-layer structure consisting of only the outer layer.
[0041] The lithium transition metal composite oxide particles of this embodiment have a higher Mn content in the composition of the outer layer than in the composition of the center. The ratio of the number of Mn atoms to the number of Ni atoms in the outer layer of the lithium transition metal composite oxide of this embodiment (Mn / Ni ratio) is 1.0 to 2.5, preferably 1.0 to 2.0, and more preferably 1.0 to 1.8. When the Mn / Ni ratio is within the above numerical range, the movement of lithium ions is not hindered, and when used as a positive electrode active material, the charge / discharge capacity of a lithium ion secondary battery is high.
[0042] The Mn / Ni ratio can be determined by quantitative analysis using X-ray photoelectron spectroscopy (XPS). XPS allows the composition of the manganese-rich surface of the entire particle to be analyzed. In other words, the analysis results obtained by XPS do not show the local composition of the entire surface of a particle, but show the composition of the entire surface of the particle.
[0043] The ratio of the number of Ni atoms to the number of Zr atoms (Ni / Zr ratio) in the outer layer of the lithium transition metal composite oxide of this embodiment is preferably 6.50 to 17.5, more preferably 6.75 to 17.5, and even more preferably 7.00 to 17.5. When the Ni / Zr ratio is within the above range, the surface is rich in zirconium (Zr). Therefore, the increase in Ni valence and the decrease in Mn valence can be suppressed, and the discharge capacity can be further improved. In addition, the cycle characteristics can be further improved. The Ni / Zr ratio can be determined by quantitative analysis using XPS.
[0044] The ratio of the number of Mn atoms to the number of Zr atoms in the outer layer of the lithium transition metal composite oxide of this embodiment (Mn / Zr ratio) is preferably 13.5 to 18.0, more preferably 13.5 to 17.5, and even more preferably 13.5 to 17.0. When the Mn / Zr ratio is within the above range, the surface is rich in zirconium (Zr). Therefore, the increase in Ni valence and the decrease in Mn valence can be suppressed, and the discharge capacity can be further improved. In addition, the cycle characteristics can be further improved. The Mn / Zr ratio can be determined by quantitative analysis using XPS.
[0045] The lithium transition metal composite oxide particles of the present embodiment may be primary particles or secondary particles. Since relatively dense particles can be obtained, the lithium transition metal composite oxide particles are preferably secondary particles formed by agglomeration of a plurality of primary particles.
[0046] <Lattice constant> The lithium transition metal composite oxide of this embodiment is a rhombohedral layered compound, and has a crystal structure of space group R-3m. The lattice constants of the lithium transition metal composite oxide are preferably an a-axis length of 2.880 Å to 2.900 Å, a c-axis length of 14.28 Å to 14.30 Å, and c / a of 4.940 to 4.960. With the lattice constants in the above ranges, the lithium transition metal composite oxide allows lithium ions to easily diffuse within the primary particles, and has low resistance. The crystal lattice constant can be determined by measuring the X-ray diffraction pattern of the lithium transition metal composite oxide and then applying the least squares method using each index and its interplanar spacing.
[0047] < 6 Li-MAS-NMR spectrum> FIG. 1 shows the solid-state lithium nuclear magnetic resonance (NMR) spectra of the lithium transition metal composite oxides according to this embodiment (Examples 1 and 2). 6 The solid line (Example 1) is the spectrum after heat treatment at 1100°C for 5 minutes, and the dashed line (Example 2) is the spectrum after heat treatment at 1100°C for 5 minutes, and then holding at 650°C for 19 hours, 550°C for 19 hours, and 450°C for 19 hours. The spectrum has a peak in the range of 500 to 800 ppm. This means that Ni and Mn in the transition metal layer adjacent to Li-O6 resulting from the Li layer are uniformly solid-dissolved, and Ni and Mn are uniformly dispersed in the lithium transition metal composite oxide, that is, Li is uniformly solid-dissolved.
[0048] In addition, the spectrum shown in FIG. 1 has no peaks other than ghost peaks such as spinning side bands in the range of 1475 to 1550 ppm. This means that there is no peak due to Li2MnO3, and indicates that there is no LiMn6 domain in the transition metal layer. When Ni and Mn are not uniformly dissolved in solid solution and a Mn-rich domain is formed, a peak due to Li2MnO3 is observed in the range of 1475 to 1550 ppm. The inventors of the present invention have found that the peaks in FIG. 6In the Li-MAS-NMR spectrum, it has been confirmed that there are no peaks other than ghost peaks in the range of 1475 to 1550 ppm by peak separation. In addition, in FIG. 1, "*" means a spinning sideband.
[0049] 6 The Li-MAS-NMR spectrum can be measured by a solid-state lithium nuclear magnetic resonance apparatus using the magic angle sample rotation method.
[0050] Since Ni, Mn, and Zr are uniformly solid-solved in the lithium transition metal composite oxide of the present embodiment, the charge-discharge capacity can be increased when used as a positive electrode active material in a lithium-ion secondary battery.
[0051] <X-ray diffraction (XRD) pattern> FIG. 2 shows the X-ray diffraction (XRD) pattern of the lithium transition metal composite oxide (Li 1.04 Ni 0.475 Mn 0.475 Zr 0.01 O2) according to the present embodiment. As the target for irradiating the electron beam, Cu (copper) is used, and as the characteristic X-ray, Kα ray is used. No peaks due to the domain structure are observed in either the pattern after heat-treating the raw material mixture at 1100 °C for 5 minutes (solid line, Example 1) or the pattern after heat-treating at 1100 °C for 5 minutes and then holding at 650 °C for 19 hours, 550 °C for 19 hours, and 450 °C for 19 hours (broken line, Example 2). In particular, the XRD pattern of the lithium transition metal composite oxide of the present embodiment has no peaks in the range of 42° ≤ 2θ ≤ 43°. This means that there are no peaks due to Li2ZrO3, indicating that Zr is solid-solved in the lithium transition metal composite oxide.
[0052] Also, in the XRD pattern of FIG. 2, the two peaks of the 108 plane and the 110 plane in the space group R-3m are cracked and clearly separated. This indicates that Ni, Mn, and Zr in the transition metal layer are uniformly dispersed without phase separation.
[0053] In FIG. 2, the half-width of the 110 plane peak in the space group R-3m is 0.10° or more and 0.21° or less. This indicates that Ni, Mn, and Zr in the transition metal layer in the lithium transition metal composite oxide do not separate into phases and are in solid solution. Note that "half-width is 0.10° or more and 0.21° or less" means that the 110 plane peak in the space group R-3m does not tail. The half-width of the peak is determined by analyzing the XRD pattern.
[0054] [Method of manufacturing positive electrode active material for lithium ion secondary batteries] The positive electrode active material for lithium ion secondary batteries of this embodiment contains the above-mentioned lithium transition metal composite oxide as a main component. As the lithium source of the lithium transition metal composite oxide, known compounds such as hydroxides such as lithium hydroxide monohydrate (LiOH·H2O), carbonates such as lithium carbonate (Li2CO3), acetates such as lithium acetate (CH3COOLi) and lithium acetate dihydrate (CH3COOLi·2H2O) can be used, and there is no particular limitation. As for the compounds of the nickel source, manganese source, and zirconium source of the transition metals, known oxides, hydroxides, or metal salts of nickel, manganese, and zirconium can be widely used, and there is no particular limitation. For example, nickel compounds that can be used include, but are not limited to, nickel hydroxide (Ni(OH)2), nickel(II) chloride (NiCl2), nickel(II) chloride hexahydrate (NiCl2·6H2O), and nickel(II) nitrate hexahydrate (Ni(NO3)2·6H2O). Examples of manganese compounds that can be used include, but are not limited to, manganese(II) chloride (MnCl2), manganese(II) chloride tetrahydrate (MnCl2·4H2O), manganese carbonate hexahydrate (MnCO3·6H2O), and manganese(II) nitrate hexahydrate (Mn(NO3)2·6H2O). Examples of the zirconium compound that can be used include, but are not limited to, zirconium dioxide (ZrO2), zirconium(IV) sulfate tetrahydrate (Zr(SO4)2·4H2O), and zirconium(IV) hydroxide (Zr(OH)4). The above transition metal compounds can be used alone or in the form of a composite hydroxide (for example, nickel manganese zirconium composite hydroxide) prepared by a coprecipitation method or the like.
[0055] The lithium transition metal composite oxide of this embodiment can be synthesized using a known method. For example, a composite hydroxide or composite oxide of a nickel compound and a manganese compound is prepared as an intermediate compound, and the intermediate compound, a zirconium compound, and a lithium compound are mixed to form a raw material mixture, and the raw material mixture is heat-treated (e.g., calcined) in a predetermined atmosphere at a predetermined temperature for a predetermined time, thereby synthesizing the oxide. In addition, a composite hydroxide or composite oxide of a nickel compound, a manganese compound, and a zirconium compound is prepared as an intermediate compound, and the intermediate compound and a lithium compound are mixed to form a raw material mixture, and the raw material mixture is heat-treated (e.g., calcined) in a predetermined atmosphere at a predetermined temperature for a predetermined time, thereby synthesizing the oxide.
[0056] The lithium transition metal composite oxide obtained in the heat treatment step is preferably further held at a predetermined temperature range for a predetermined time in a slow cooling step. The slow cooling conditions vary depending on the treatment conditions (for example, heat treatment atmosphere such as oxygen atmosphere, air atmosphere, etc.), and are preferably adjusted appropriately. The present inventors have found that by appropriately selecting the heat treatment conditions and the slow cooling conditions, the transition metals of the lithium transition metal composite oxide can be uniformly dispersed and the Mn / Ni ratio of the particle surface can be increased. Hereinafter, the manufacturing method of the positive electrode active material for lithium ion secondary batteries of this embodiment will be described in more detail with reference to the embodiment.
[0057] "First step" In the first step, a predetermined amount of zirconium compound and a predetermined amount of lithium compound are first added to an intermediate nickel manganese compound, and then dispersed and mixed in a solvent such as ethanol. It is to be noted that a predetermined amount of the intermediate compound, a predetermined amount of zirconium compound, and a predetermined amount of lithium compound may be mixed by dry mixing without using a solvent, as well as wet mixing using a solvent. For example, zirconium dioxide (ZrO2) is used as the zirconium compound, and lithium carbonate (Li2CO3) is used as the lithium compound, and Li 1.04 Ni 0.475 Mn 0.475 Zr 0.01 When synthesizing O2, Li2CO3 is weighed out in an amount preferably 1% by mass to 5% by mass, for example 2% by mass more than the stoichiometric ratio. 1.02 Ni 0.475 Mn 0.475 Zr 0.01 Similarly, when synthesizing O2, Li2CO3 is weighed out in an amount preferably 1 mass % to 5 mass %, for example 2 mass %, more than the stoichiometric ratio.
[0058] The nickel manganese compound can be synthesized by a known method. When the nickel manganese compound is a hydroxide, for example, nickel sulfate hexahydrate (NiSO4·6H2O) and manganese sulfate pentahydrate (MnSO4·5H2O) are weighed out so that the molar ratio of Ni:Mn is 1:1, and pure water is added to dissolve the compound. Then, an alkaline aqueous solution is dropped into the sulfate aqueous solution to co-precipitate the compound as a nickel manganese composite hydroxide.
[0059] Instead of using the nickel manganese compound as the intermediate compound, a nickel manganese zirconium compound may be used. For example, a predetermined amount of a lithium compound is added to a nickel manganese zirconium compound, and the compound is dispersed and mixed in a solvent such as ethanol. In addition to wet mixing using a solvent, a predetermined amount of the nickel manganese zirconium compound and a predetermined amount of a lithium compound may be mixed by dry mixing without using a solvent. For example, lithium carbonate (Li2CO3) is used as the lithium compound, and Li 1.04 Ni 0.475 Mn0.475 Zr 0.01 When synthesizing O2, Li2CO3 is weighed out in an amount preferably 1% by mass to 5% by mass, for example 2% by mass more than the stoichiometric ratio. 1.02 Ni 0.475 Mn 0.475 Zr 0.01 Similarly, when synthesizing O2, Li2CO3 is weighed out in an amount preferably 1 mass % to 5 mass %, for example 2 mass %, more than the stoichiometric ratio.
[0060] The nickel manganese zirconium compound can be synthesized by using a known method. When the nickel manganese zirconium compound is a hydroxide, for example, nickel sulfate hexahydrate (NiSO4·6H2O), manganese sulfate pentahydrate (MnSO4·5H2O), and zirconium (IV) sulfate tetrahydrate (Zr(SO4)2·4H2O) are weighed out so that the molar ratio of Ni:Mn:Zr is 1:1:x (x is preferably 0.005 to 0.04), and pure water is added to dissolve the compound, and then an alkaline aqueous solution is dropped into the sulfate aqueous solution to co-precipitate the compound as a nickel manganese zirconium composite hydroxide.
[0061] As the precursor, a mixture of a lithium compound, a zirconium compound, and a nickel manganese compound, or a mixture of a lithium compound and a nickel manganese zirconium compound is crushed to a desired size, mixed, and then filled into a crucible and the mixture is heat-treated. As the crucible, an alumina sagger, an alumina crucible, a platinum crucible, a gold crucible, or the like is used. For example, a firing furnace or a roller hearth kiln is used for the heat treatment of the mixture.
[0062] The mixture placed in a sagger or crucible is heated at a temperature rise rate of 5°C / min to 25°C / min, preferably 10°C / min to 25°C / min, until the heat treatment temperature is reached. The heat treatment atmosphere is not particularly limited, and examples thereof include air (air atmosphere) and oxygen flow. The heat treatment atmosphere is preferably oxygen flow. The heat treatment time can be appropriately set depending on the heat treatment temperature. The heat treatment time means the time during which the heat treatment temperature is maintained.
[0063] When a mixture of a lithium compound (e.g., Li2CO3), a zirconium compound (e.g., ZrO2), and a nickel manganese compound is heat-treated, the heat treatment temperature is preferably 1025° C. or more and 1150° C. or less, more preferably 1050° C. or more and 1125° C. or less. The heat treatment time is preferably 1 minute or more and 7 hours or less, more preferably 2 minutes or more and 6 hours or less, even more preferably 3 minutes or more and 5 hours or less, and particularly preferably 5 minutes or more and 3 hours or less.
[0064] Furthermore, when a mixture of a lithium compound (e.g., Li2CO3) and a nickel manganese zirconium compound is heat-treated, the heat treatment temperature is preferably from 1025° C. to 1150° C., more preferably from 1050° C. to 1125° C. The heat treatment time is preferably from 1 minute to 7 hours, more preferably from 2 minutes to 6 hours, even more preferably from 3 minutes to 5 hours, and particularly preferably from 5 minutes to 3 hours.
[0065] "Second step" In the second step, the powder obtained after the heat treatment in the first step is cooled to 800° C. at a temperature drop rate of 5° C. / min to 25° C. / min, preferably 10° C. / min to 25° C. / min, and then the powder is held at 800° C. for 0.5 to 12 hours. The atmosphere in which the powder is held at 800° C. is not particularly limited, and examples thereof include the air (air atmosphere), air flow, and oxygen flow.
[0066] The method for producing a positive electrode active material for a lithium ion secondary battery according to the present embodiment may include a step of holding the powder at 750° C. for 0.5 to 12 hours after the second step. In this case, the powder held at 800° C. in the second step is cooled to 750° C. at a temperature drop rate of 10° C. / min, and then the powder is held at 750° C. for 0.5 to 12 hours. The atmosphere in which the powder is held at 750° C. is not particularly limited, and examples thereof include air (air atmosphere), air flow, and oxygen flow.
[0067] "The third step" In the third step, the powder held at 750° C. in the second step is cooled to 700° C. at a temperature drop rate of 5° C. / min to 25° C. / min, preferably 10° C. / min to 25° C. / min, and then the powder is held at 700° C. for 0.5 to 12 hours. The atmosphere in which the powder is held at 700° C. is not particularly limited, and examples thereof include the air (air atmosphere), air flow, and oxygen flow.
[0068] "The fourth step" In the fourth step, the powder held at 700° C. in the third step is cooled to 650° C. at a temperature drop rate of 5° C. / min to 25° C. / min, preferably 10° C. / min to 25° C. / min, and then the powder is held at 650° C. for 0.5 to 12 hours. The atmosphere in which the powder is held at 650° C. is not particularly limited, and examples thereof include the atmosphere (air atmosphere), air flow, and oxygen flow.
[0069] "The fifth step" In the fifth step, the powder held at 650° C. in the fourth step is cooled to 600° C. at a temperature drop rate of 5° C. / min to 25° C. / min, preferably 10° C. / min to 25° C. / min, and then the powder is held at 600° C. for 0.5 to 20 hours. The atmosphere in which the powder is held at 600° C. is not particularly limited, and examples thereof include the air (air atmosphere), air flow, and oxygen flow.
[0070] "The sixth step" In the sixth step, the powder held at 600°C in the fifth step is cooled at a temperature drop rate of 10°C / min to reach 400°C to 500°C, and then the powder is held at 400°C to 500°C for 0.5 to 30 hours. The sixth step may be a step of holding the powder at 450°C for 0.5 to 30 hours, and then holding the powder at 400°C for 0.5 to 30 hours. The sixth step may also be a step of holding the powder at 500°C for 0.5 to 20 hours.
[0071] The slow cooling steps in the second to sixth steps described above can be appropriately changed or omitted as necessary. In one embodiment, the slow cooling step is preferably held at 450°C or higher and 800°C or lower after the heat treatment, preferably for 1 hour to 24 hours, more preferably for 2 hours to 20 hours, and most preferably for 19 hours. The slow cooling step may be carried out two or more times as long as the temperature is gradually lowered. The positive electrode active material for lithium ion secondary batteries of this embodiment can further increase the Mn / Ni ratio on the particle surface of the lithium transition metal composite oxide by appropriately selecting the slow cooling conditions.
[0072] [Lithium-ion secondary battery] The lithium ion secondary battery of the present embodiment includes a positive electrode, a negative electrode, and an electrolyte, and the positive electrode contains a positive electrode active material mainly composed of the above-mentioned lithium transition metal composite oxide. The lithium ion secondary battery of the present embodiment may include other battery elements as necessary.
[0073] The lithium ion secondary battery of this embodiment can use the battery elements of known lithium ion secondary batteries as they are, except that the positive electrode contains the above-mentioned positive electrode active material mainly composed of the lithium transition metal composite oxide. The lithium ion secondary battery of this embodiment may be of any of the following types: coin type, button type, cylindrical type, square type, and laminate type. The lithium ion secondary battery of this embodiment can be used in a wide range of applications, such as for mobile devices such as mobile phones and notebook computers, and for in-vehicle use.
[0074] Hereinafter, the lithium ion secondary battery of this embodiment will be described as a lithium ion secondary battery using an electrolyte (coin type lithium ion secondary battery). Each battery element described below can be similarly applied to an all-solid-state lithium ion secondary battery that does not use an electrolyte.
[0075] Fig. 3 is a cross-sectional view showing a schematic diagram of the lithium ion secondary battery according to the present embodiment. Fig. 3 shows an example of the lithium ion secondary battery according to the present embodiment as a coin-type lithium ion secondary battery. As shown in Fig. 3, the lithium ion secondary battery 1 according to the present embodiment includes a negative electrode can (negative electrode terminal) 20, a negative electrode 3, a separator 4 impregnated with an electrolyte, an insulating packing (gasket) 5, a positive electrode 2, and a positive electrode can 10.
[0076] The positive electrode can 10 is disposed below the separator 4, and the negative electrode can 20 is disposed above the separator 4, with the positive electrode can 10 and the negative electrode can 20 forming the outer shape of the lithium-ion secondary battery 1. A positive electrode 2 and a negative electrode 3 are provided between the positive electrode can 10 and the negative electrode can 20 via a separator 4 impregnated with an electrolyte, and the positive electrode 2 and the negative electrode 3 are separated by the separator 4. The positive electrode can 10 and the negative electrode can 20 are electrically insulated by an insulating packing 5.
[0077] The lithium ion secondary battery 1 can be manufactured by preparing a positive electrode mixture by mixing a conductive agent, a binder, etc. with the positive electrode active material for lithium ion secondary batteries of this embodiment as necessary, and pressing this onto a current collector (not shown) to produce a positive electrode 2. As the current collector, preferably, a stainless steel mesh, an aluminum foil, etc. can be used. As the conductive agent, preferably, acetylene black, Ketchen black, etc. can be used. As the binder, preferably, tetrafluoroethylene, polyvinylidene fluoride, etc. can be used.
[0078] The blending of the positive electrode active material, conductive agent, and binder in the positive electrode mixture is not particularly limited. The content of the conductive agent in the positive electrode mixture is preferably 1 mass% to 15 mass%, more preferably 0.1 mass% to 5 mass%. The content of the binder in the positive electrode mixture is preferably 0.1 mass% to 10 mass%, more preferably 0.1 mass% to 5 mass%. It is preferable to blend the positive electrode active material, conductive agent, and binder so that the remainder of the positive electrode mixture (a portion other than the positive electrode active material and conductive agent) becomes the positive electrode active material.
[0079] In the lithium ion secondary battery 1, the negative electrode 3 for the positive electrode 2 may be made of any of the known materials that function as a negative electrode active material and can absorb and release lithium, such as metal-based materials such as metallic lithium and lithium alloys, carbon-based materials such as graphite and MCMB (mesocarbon microbeads), and silicon-based materials such as silicon (Si), Si alloys, and silicon oxide.
[0080] The separator 4 and the battery container (positive electrode can 10, negative electrode can 20) may be made of known battery elements.
[0081] The electrolyte may be a known electrolytic solution, solid electrolyte, etc. The electrolytic solution may be, for example, a solution in which an electrolyte such as lithium perchlorate or lithium hexafluorophosphate is dissolved in a solvent such as ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate (PC), or diethyl carbonate (DEC).
[0082] In addition, the all-solid-state lithium ion secondary battery can have the same structure as a known all-solid-state lithium ion secondary battery, except that a positive electrode active material containing the above-mentioned lithium transition metal composite oxide as a main component is used.
[0083] In the case of an all-solid-state lithium ion secondary battery, the electrolyte may be, for example, a polymer-based solid electrolyte such as a polyethylene oxide-based polymer compound, a polymer compound containing at least one of a polyorganosiloxane chain or a polyoxyalkylene chain, a sulfide-based solid electrolyte, or an oxide-based solid electrolyte.
[0084] For the positive electrode of the all-solid-state lithium ion secondary battery, for example, a positive electrode mixture containing a solid electrolyte in addition to the above-mentioned positive electrode active material, conductive agent, and binder can be supported on a positive electrode current collector made of aluminum, nickel, stainless steel, or the like.
[0085] The lithium ion secondary battery 1 of this embodiment can have a high capacity because the positive electrode 2 contains a positive electrode active material containing the above-mentioned lithium transition metal composite oxide as a main component. EXAMPLES
[0086] Examples of the present invention will be described below, but the present invention is not limited to the following examples.
[0087] [Example 1] (Synthesis of lithium nickel manganese zirconium oxide: Li 1.04 Ni 0.475 Mn 0.475 Zr 0.01 O2) Li2CO3 (Kojundo Kagaku), Ni 0.5 Mn 0.5 Li(OH)2 and Zr(OH)4 (Sigma-Aldrich) were weighed out so that the molar ratio of Li:Ni:Mn:Zr was 1.04:0.475:0.475:0.01. Taking into account the evaporation of Li, Li2CO3 was weighed out so that there was 3% more by mass than Li2CO3 based on the stoichiometric ratio. 0.5 Mn 0.5 The total mass of Zr(OH)2 and Zr(OH)4 (Sigma-Aldrich) was 2.1 g. These were dispersed in ethanol in a mortar and mixed. Then, the mixture was filled into a platinum crucible of JIS standard. Using a calcination furnace, the mixture filled into the platinum crucible was heated in air at a temperature increase rate of 15°C / min, and calcined at 1100°C for 5 minutes. After that, the obtained powder was left to stand until the temperature reached room temperature (25°C), and the lithium nickel manganese zirconium oxide of Example 1 was obtained.
[0088] [Example 2] (Synthesis of lithium nickel manganese zirconium oxide: Li 1.04 Ni 0.475 Mn 0.475 Zr 0.01 O2) Li2CO3 (Kojundo Kagaku), Ni 0.5 Mn 0.5Li(OH)2 and Zr(OH)4 (Sigma-Aldrich) were weighed out so that the molar ratio of Li:Ni:Mn:Zr was 1.04:0.475:0.475:0.01. Taking into account the evaporation of Li, Li2CO3 was weighed out so that there was 3% more by mass than Li2CO3 based on the stoichiometric ratio. 0.5 Mn 0.5 The total mass of Zr(OH)2 and Zr(OH)4 (Sigma-Aldrich) was 2.1 g. These were dispersed in ethanol in a mortar and mixed. Then, the mixture was filled into a platinum crucible of JIS standard. Using a calcination furnace, the mixture filled into the platinum crucible was heated in air at a temperature increase rate of 15°C / min and calcined at 1100°C for 5 minutes to obtain a powder of lithium nickel manganese zirconium oxide. The powder after the heat treatment was cooled to 650°C at a temperature drop rate of 10°C / min, and then the powder was held in air at 650°C for 19 hours. Next, the powder was cooled to 550°C at a temperature drop rate of 10°C / min, and then the cooled powder was held in air at 550°C for 19 hours. Further, the powder was cooled to 450°C at a temperature drop rate of 10°C / min, and then the cooled powder was held in air at 450°C for 19 hours. Then, the powder was left to stand until the temperature reached room temperature (25°C), and the lithium nickel manganese zirconium oxide of Example 2 was obtained.
[0089] [Example 3] (Synthesis of lithium nickel manganese zirconium oxide: Li 1.02 Ni 0.57 Mn 0.40 Zr 0.01 O2) Li2CO3 (Kojundo Kagaku), Ni(OH)2 (Kojundo Kagaku), Ni 0.5 Mn 0.5 Li2CO3 (Kojundo Chemical), Ni(OH)2 (Kojundo Chemical), and Ni(OH)4 (Sigma-Aldrich) were weighed out so that the molar ratio of Li:Ni:Mn:Zr was 1.02:0.57:0.40:0.01. Taking into account the evaporation of Li, Li2CO3 was weighed out so that there was 2% more by mass based on the stoichiometric ratio. 0.5 Mn 0.5The total mass of Zr(OH)2 and Zr(OH)4 (Sigma-Aldrich) was 2.1 g. These were dispersed in ethanol in a mortar and mixed. Then, the mixture was filled into a platinum crucible of JIS standard. Using a calcination furnace, the mixture filled into the platinum crucible was heated in air at a temperature increase rate of 15°C / min, and calcined at 1050°C for 30 minutes. After that, the obtained powder was left to stand until the temperature reached room temperature (25°C), and the lithium nickel manganese zirconium oxide of Example 3 was obtained.
[0090] [Comparative Example 1] (Synthesis of lithium nickel manganese oxide: Li 1.04 Ni 0.48 Mn 0.48 O2) Li2CO3 (Kojundo Kagaku), Ni 0.5 Mn 0.5 Li2CO3 (manufactured by Kojundo Chemical Co., Ltd.) was weighed out so that the molar ratio of Li:Ni:Mn was 1.04:0.48:0.48, and Li2CO3 was weighed out so that the amount was 2% more by mass based on the stoichiometric ratio, taking into account the evaporation of Li. 0.5 Mn 0.5 The total mass of (OH)2 (manufactured by NARD) was 2.1 g. These were dispersed in ethanol in a mortar and mixed. Then, the mixture was filled into a platinum crucible of JIS standard. Using a firing furnace, the mixture filled into the platinum crucible was heated in air at a temperature increase rate of 15°C / min, and fired at 950°C for 30 minutes. After that, the obtained powder was left to stand until the temperature reached room temperature (25°C), and the lithium nickel manganese oxide of Comparative Example 1 was obtained.
[0091] (analysis) The chemical composition of the sample obtained in Example 1 was analyzed using an ICP emission spectrometer (product name: Agilent5110 VDV, manufactured by Agilent Technologies), and the results are shown in Table 1. As shown in Table 1, it was confirmed that the composition was Li:Ni:Mn:Zr=1.04:0.475:0.475:0.01. In addition, the X-ray diffraction (XRD) pattern of the obtained sample was measured using a powder X-ray diffractometer (product name: SmartLab, manufactured by Rigaku). Cu (copper) was used as the target for irradiating the electron beam, and Kα rays were used as the characteristic X-rays. The lattice constant was calculated by the least squares method using each index of the obtained XRD pattern and its interplanar spacing. The space group of the obtained sample was R-3m, and the lattice constant was calculated to be a = 2.88560 (4) Å, c = 14.2857 (3) Å, and c / a = 4.9502. The half-width of the peak of the 110 plane in the space group R-3m was 0.1079 (17) °. The powder X-ray diffraction pattern is shown in Figure 2. The lattice constants and half-width of the peaks are shown in Table 1. We also have an X-ray photoelectron spectroscopy (XPS) analyzer (product name: K-Alpha + The composition of the surface layer of the obtained sample was analyzed by quantitative analysis using a 3000 MPa (Thermo Fisher Scientific) and the results are shown in Table 1. As shown in Table 1, the Mn / Ni ratio in the surface layer was 1.0. The measurement conditions for the XPS measurement are as follows: <XPS measurement conditions> Model used: Thermo Fisher Scientific, K-Alpha + (Product name) X-ray irradiation: Single crystal spectrometer AlKα (12 keV, 72 W) X-ray spot diameter: 400 μm Neutralization gun: Used Reference spectrum: CC, CH 284.6 eV Detection depth: 6~7nm
[0092] Furthermore, the obtained samples of Example 1 and Example 2 were analyzed by Li-MAS-NMR (product name: AVANCE300, manufactured by Bruker). The results are shown in FIG. 1. From the results shown in FIG. 1, 6 It was confirmed that the samples of Example 1 and Example 2 had peaks in the range of 500 to 800 ppm in the Li-MAS-NMR spectrum. Moreover, it was confirmed that the samples of Example 1 and Example 2 had no peaks other than the spinning side bands in the range of 1475 to 1550 ppm.
[0093] The samples obtained in Examples 2 to 3 and Comparative Example 1 were also subjected to ICP emission spectrometry, powder X-ray diffraction measurement, XPS analysis, and 6 Li-MAS-NMR measurement was carried out. The results are shown in Table 1, Figure 2, Figure 5 and Figure 6. In Table 1, "peak half width (°)" represents the half width of the peak of the 110 plane in the space group R-3m.
[0094] [Table 1]
[0095] From the XRD patterns shown in Fig. 2, it was confirmed that the samples of Example 1 and Example 2 did not have a peak in the range of 42°≦2θ≦43°. It was also confirmed that the peaks of the 108 and 110 planes in the space group R-3m were split in the samples of Example 1 and Example 2. Furthermore, as shown in Table 1, the half-width of the peak of the 110 plane in the space group R-3m in the samples of Example 1 and Example 2 was 0.10° or more and 0.21° or less.
[0096] As shown in Figure 5, 6 In the Li-MAS-NMR spectrum, it was confirmed that the sample of Example 3 had a peak in the range of 500 to 800 ppm. In addition, it was confirmed that the sample of Example 3 had no peaks other than the spinning side band in the range of 1475 to 1550 ppm. In contrast, the sample of Comparative Example 1, which does not contain zirconium in its chemical composition and has an outer layer with an Mn / Ni ratio of less than 1.0, 6 In the Li-MAS-NMR spectrum, a peak was observed in the range of 1475 to 1550 ppm, although there was a peak in the range of 500 to 800 ppm.
[0097] As shown in Fig. 6, it was confirmed that the sample of Example 3 had no peak in the range of 42°≦2θ≦43°. It was also confirmed that the peaks of the 108 plane and the 110 plane in the space group R-3m were split in the sample of Example 3. Furthermore, as shown in Table 1, the half-width of the peak of the 110 plane in the space group R-3m in the sample of Example 3 was 0.10° or more and 0.21° or less. In contrast, the sample of Comparative Example 1, which does not contain zirconium in its chemical composition and has an outer layer with a Mn / Ni ratio of less than 1.0, does not have a peak in the range of 42°≦2θ≦43°, but no split was confirmed in the peaks of the 108 and 110 planes in the space group R-3m.
[0098] [Preparation of lithium-ion secondary batteries] The lithium nickel manganese zirconium oxides of Examples 1 to 3 and the lithium nickel manganese oxide of Comparative Example 1 were used as the positive electrode active material, and acetylene black (AB) as the conductive agent and polyvinylidene fluoride (PVDF) as the binder were mixed in a weight ratio of 8:1:1 using NMP (N-methyl-2-pyrrolidone) as a solvent to prepare a slurry. The mixture was then coated on an aluminum foil with a thickness of 15 μm and dried to prepare a positive electrode with a diameter of 14 mm. The coating area density was 4.5 mg / cm. 2 , volume density is 2.3g / cm 3 The positive electrode was used as a counter electrode of lithium metal with a thickness of 200 μm and a diameter of 16 mm, and a polyethylene microporous membrane with a thickness of 20 μm and a diameter of 18 mm was used as a separator. The electrolyte was a 1.2 mol / L solution of lithium hexafluorophosphate (LiPF6) dissolved in a mixed solvent (volume ratio 3:4:3) of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC), and a lithium ion secondary battery (2032 coin cell) with the structure shown in FIG. 3 was fabricated. The battery was fabricated according to the known cell configuration and assembly method.
[0099] [Charge / discharge test] For each of the lithium-ion secondary batteries prepared, a charge-discharge test was performed at a temperature of 25°C, a constant current of 0.05C (1C: 250 mA / g), a current density of 12.5mA / g, and a cutoff potential of 4.7V to 2.5V or 4.8V to 2.5V, to evaluate the initial discharge capacity. The charge-discharge test started with charging.
[0100] Fig. 4 shows charge / discharge curves in Examples 1 and 2. Fig. 4 shows voltage changes during discharge, in which the cell voltage decreases as the capacity increases, and voltage changes during charge, in which the cell voltage increases as the capacity increases.
[0101] As shown in Fig. 4, it was found that the lithium ion secondary battery using the lithium nickel manganese zirconium oxide of Example 2 as the positive electrode active material has a higher capacity than the lithium ion secondary battery using the lithium nickel manganese zirconium oxide of Example 1 as the positive electrode active material. This is presumably because the stepwise slow cooling process in Example 2 makes the structure of the lithium nickel manganese zirconium oxide more stable, suppresses the dissolution of Ni into the electrolyte, and increases the Mn / Ni ratio in the outer layer of the lithium nickel manganese zirconium oxide particles. It is expected that the capacity of Example 1 will be higher if the heat treatment conditions are appropriately set.
[0102] Fig. 7 shows charge / discharge curves in Example 3 and Comparative Example 1. Fig. 7 shows voltage changes during discharge, in which the cell voltage decreases as the capacity increases, and voltage changes during charge, in which the cell voltage increases as the capacity increases.
[0103] As shown in FIG. 7, it was found that the lithium ion secondary battery using the lithium nickel manganese zirconium oxide of Example 3 as a positive electrode active material had a higher capacity than the lithium ion secondary battery using the lithium nickel manganese oxide of Comparative Example 1 as a positive electrode active material.
[0104] [Cycle test] After evaluating the initial discharge capacity, each of the lithium ion secondary batteries produced was subjected to a cycle test 100 times under the temperature condition of 25°C, a current density of 12.5mA / g, and a cutoff potential of 4.3V to 2.5V, and the capacity retention rate (100th cycle discharge capacity / 1st cycle discharge capacity) was evaluated. The charge / discharge test started with charging. The results are shown in Table 1. The higher the capacity retention rate, the better the cycle characteristics.
[0105] As shown in Table 1, the lithium ion secondary batteries of Examples 1 to 3 to which the present invention was applied exhibited a high capacity retention rate of 95% or more. In contrast, the capacity retention rate of the lithium ion secondary battery of Comparative Example 1, which did not contain zirconium in its chemical composition and had an Mn / Ni ratio in the outer layer of less than 1.0, was 88%.
[0106] From the above results, it is apparent that the present invention can provide a positive electrode active material for a lithium ion secondary battery that can further increase the discharge capacity, and a lithium ion secondary battery that includes the positive electrode active material. [Explanation of symbols]
[0107] 1...Lithium-ion secondary battery 2...Positive electrode 3...Negative electrode 4…Separator 5...Insulating packing (gasket) 10…Positive electrode can 20...Negative electrode can (negative electrode terminal)
Claims
1. A positive electrode active material for a lithium ion secondary battery, the positive electrode active material comprising a lithium transition metal composite oxide as a main component, The lithium transition metal composite oxide is in the form of particles having an outer layer on the surface thereof, The lithium transition metal composite oxide is represented by the following formula (1): Li m Ni x Mn y Zr z O 2 (1) (In formula (1), m is in the range of 1.0≦m≦1.04, x is in the range of 0.47<x<0.58, y is in the range of 0.40≦y<0.50, and z is in the range of 0<z<0.02.) A positive electrode active material for a lithium ion secondary battery, wherein a ratio of the number of Mn atoms to the number of Ni atoms in the outer layer (Mn / Ni ratio) is 1.0 or more and 2.5 or less.
2. 2. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein a ratio of the number of Ni atoms to the number of Zr atoms in the outer layer (Ni / Zr ratio) is 6.50 or more and 17.5 or less.
3. Solid-state lithium nuclear magnetic resonance analysis using magic angle sample spinning ( 6 The positive electrode active material for lithium ion secondary batteries according to claim 1, wherein the spectrum of the lithium transition metal composite oxide measured by Li-MAS-NMR has a peak in the range of 500 to 800 ppm.
4. Solid-state lithium nuclear magnetic resonance analysis using magic angle sample spinning ( 6 2. The positive electrode active material for lithium ion secondary batteries according to claim 1, wherein the spectrum of the lithium transition metal composite oxide measured by Li-MAS-NMR has no peak in the range of 1475 to 1550 ppm.
5. 2. The positive electrode active material for a lithium ion secondary battery according to claim 1, which has no peak in the range of 42°≦2θ≦43° in an X-ray diffraction pattern using a Cu radiation source.
6. 2. The positive electrode active material for lithium ion secondary batteries according to claim 1, wherein in an X-ray diffraction pattern using a Cu radiation source, the peaks of the 108 plane and the 110 plane in the space group R-3m are split, and the half-width of the peak of the 110 plane is 0.10° or more and 0.21° or less.
7. The lattice constants (a, c, c / a) of the lithium transition metal composite oxide in the space group R-3m are such that the a-axis length is 2.880 Å to 2.900 Å, the c-axis length is 14.28 Å to 14.30 Å, and c / a is 4.940 to 4.
960. The positive electrode active material for lithium ion secondary batteries according to claim 1.
8. A lithium ion secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode contains the positive electrode active material for lithium ion secondary batteries according to any one of claims 1 to 7.
9. A method for producing a positive electrode active material for a lithium ion secondary battery according to any one of claims 1 to 7, A method for producing a positive electrode active material for a lithium ion secondary battery, comprising a step of heat-treating a mixture of a lithium compound, a zirconium compound, and a nickel manganese compound, or a mixture of a lithium compound and a nickel manganese zirconium compound, at 1025° C. or higher and 1150° C. or lower for 1 minute to 7 hours.
10. The method for producing a positive electrode active material for a lithium ion secondary battery according to claim 9, further comprising the step of subsequently holding the obtained lithium transition metal composite oxide at 450° C. or more and 800° C. or less for 1 hour or more and 24 hours or less after the heat treatment step.
Citation Information
Patent Citations
Lithium ion battery positive plate using cobalt-free high-nickel positive electrode material
CN112382734A
Positive electrode material, preparation method thereof and lithium ion battery
CN115763760A
Nonaqueous electrolyte secondary battery
JP2007188703A
Nickel manganese composite hydroxide particle and production method thereof, positive electrode active material for nonaqueous electrolyte secondary battery and production method thereof, and nonaqueous electrolyte secondary battery
JP2012256435A
Nickel-manganese composite hydroxide particles, method for producing same, positive electrode active material for nonaqueous electrolyte secondary batteries, method for producing positive electrode active material for nonaqueous electrolyte secondary
WO2012131881A1